Toxicity Test Of Ethanol Extract Of Pletekan Leaves (Ruellia tuberosa L) Using The Brine Shrimp Lethality Test (BSLT) Method - Fajri, Fajrilda Aqilah; ridwanto, ridwanto; Pulungan, Ainil Fithri; Rani, Zulmai (Pustaka Media Publishing, 2024)
The pletekan plant (Ruellia tuberosa L.) is a family of Acanthaceae Ruellia tuberosa L.) one of the plants used as a medicinal plant, especially the leaves, have been used empirically for therapy as a diuretic, antidiabetic, antihypertensive. Also used in the treatment of syphilis, kidney stones, cancer, heart disease, colds, hypertension and digestive problems. The purpose of this study was to determine the toxicity by determining the LC50 in the ethanol extract of pletekan leaves (Ruellia tuberosa L). The analysis carried out was a toxicity test on the ethanol extract of pletekan leaves against Artemia Salina Leach shrimp larvae using the BSLT method with various concentrations, namely 10, 15, 20, 25, 30, 35, and 40 ppm and determining the LC50 value with probit analysis. Based on the results of the toxicity test, the LC50 value was 96.4595 µg/Ml. These results show that the ethanol extract of pletekan leaves (Ruellia tuberosa L) has a toxic effect on Artemia Salina Leach shrimp larvae.